STIMULATION OF CHILDREN'S GROSS MOTOR SKILLS THROUGH TRADITIONAL ENGKLEK GAMES IN GROUP B OF BINA ANAPSARA KINDERGARTEN, SAMARAN VILLAGE, TAMBELANGAN DISTRICT, SAMPANG REGENCY - Mutiatul Muzayyanah (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Children's motor skills develop from birth, so they require continuous stimulation to support their growth and development. Traditional games are said to be one of the effective ways to stimulate the development of gross motor skills in children. This study aims to analyze the stimulation of children's gross motor skills through the traditional game of engklek in group B at Bina Anapsara Kindergarten, Samaran Village, Tambelangan District, Sampang Regency. The background is the low physical activity of children due to excessive use of technology, so active and fun learning methods are needed. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. The subjects of the study were 19 children in group B. The results of the study show that engklek games can improve children's gross motor skills, especially in terms of balance, muscle strength coordination, and agility. In addition, it has a positive impact on children's emotional aspects. Thus, the traditional game of engklek is effective in being used as a learning medium in developing gross motor skills in early childhood.